DETERMINAN STRUKTUR MODAL: ANALISIS SEBELUM DAN PADA MASA COVID-19 - Dwiyanti, Rosalia Elsa; Handoko, Jesica (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
Companies must be able to combine their capital structure through internal and external funding to maximize company value while minimizing costs. This research examines the factors of ownership structure, asset structure, and liquidity on capital structure and differences in influence before and during the Covid-19 pandemic. This research uses a quantitative design with multiple linear regression analysis. Testing was carried out on manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period with a sample of 447 data with a distribution of 228 data for 2018-2019 and 219 data for 2020-2021. The study's results proved that institutional ownership and managerial ownership did not affect capital structure, capital structure was negatively affected by asset structure, and liquidity was negatively affected. No differences in ownership, asset structure, or liquidity were found before and during the Covid-19 pandemic. The results of this research provide relevant theoretical contributions to agency theory, pecking order theory, and relevant trade-off theory.